Pelatihan Skrining Penyakit Tidak Menular dan Pencegahannya Bagi Kader Kesehatan - Tri Wulandari Kesetyaningsih; Suryanto; Yoni Astuti (Universitas Serang Raya, 2022)
Non-communicable disease (NCD) screening training aims to provide skills in determining a person's health condition based on body mass index (BMI) and simple blood tests. Health cadres who have been equipped with the skills to determine BMI and simple blood tests can then detect NCD in the community independently. Nutrition training aims to provide skills in calculating nutritional adequacy from a daily menu. Educational videos on simple blood tests were made to replace hands-on training due to limitations of the covid19 protocol. Before and after training, pre and posttest were carried out. The training was attended by 15 health cadres in Gamping Kidul Village, Ambarketawang, Gamping, Sleman, Yogyakarta. The average score before training was 67.14, increasing to 73.57 thereafter. Paired T-test analysis showed no significant difference in pre and posttest scores (p = 0.076). After receiving the training, it is hoped that health cadres can carry out screening independently around their respective homes, so that early detection of NCD in the community can take place, then prevention can be carried out so that it does not become a fatal complication. It was concluded that the training could improve health cadres' understanding of PTM screening, prevention and calculating a balanced nutritious diet but not significant.